Preparation of ZnO Microflowers from a Single Source Reactant - Mi, Liwei; Chen, Weihua; Yang, Fengling; Zhang, Jianmin; Shen, Changyu; Zheng, Zhi (Asian Journal of Chemistry, 2010)
[Zn(phen)2(H2O)2]2L·6H2O (1), where HL = 4-methylbenzenesulfonic acid and phen = ophenanthroline was used as a single source reactant to prepare well-crystallized ZnO in aqueous solution of sodium hydroxide at 180 ºC under wide-range pH value for a day without the assistance of a surfactant or microemulsion. The decomposition products from this zinc inclusion complex could keep well-faceted prismatic whiskers in wide range of alkalinity. The ZnO crystal growth mechanism based on the growth units of [Zn(phen)4(H2O)2]2- is employed to explain the formation of the six different ZnO microcrystals because of the strong coordination ability between the central zinc metal ion and o-phenanthroline.